Optimization of thermosetting composites pultrusion - U Win Tun (2008)
In this investigation, the effect of two initial process conditions, pre-heating temperature of the composite and the die-cooler temperature, on the optimization of the pultrision process is discussed. The process simulation was carried out using the three-dimensional FE/NCV procedure.